Assessing maternity care access: impacts on cesarean sections and dystocia - Soo Hyun Kang; Minah Park; Jong Youn Moon; Suk Young Kim (BMC, 2024)
Abstract Background As South Korea grapples with a declining birthrate, maternity care accessibility has become challenging. This study examines the association with labour intervention and pregnancy complication, specifically focusing on C-section and dystocia in maternity disparities. Methods Data from the South Korean NHIS-NID was used to analyze 1,437,186 women with childbirths between 2010 and 2015. The research defines 50 specific districts as Obstetrically Underserved Areas produced by the Ministry of Health and Welfare in 2011. C-Section were assessed through using medical procedure and DRG codes, while dystocia was defined using ICD-10 code. Logistic regression analysis was used to examine the significance of the association. Results Among the population residing in underserved areas, 42,873 out of a total of 1,437,186 individuals were identified. For nationwide cases, the odds ratios (ORs) for C-Section were 1.11 (95% CI: 1.08-1.13) and dystocia were 1.07 (95% CI: 1.05-1.09). In relatively accessible urban areas, the ORs for C-Section and dystocia, based on whether they were obstetrically underserved areas, were 1.16 (95% CI: 1.13-1.18) and 1.10 (95% CI: 1.08-1.19), respectively. Conclusion Poor accessibility to maternity care facilities is closely linked to high-risk pregnancies, including an increased incidence of dystocia and a higher rate of C-sections. Insufficient access to maternity care not only raises the risk of serious pregnancy complications. Consequently, there is a pressing need for multi-faceted efforts to bridge this disparity.